(untitled) (Journal of Parents and Teachers, 2014)
when school year ends, students and teachers must ask themselves two questions: why they work and if they are satisfied with their work. On this hand, according to Frederick Herzberg, there are two stimuli for work: hygiene and motivation. Both have advantages that help analyzing the two previous questions. On the other hand, the job enrichment” hypothesis based on the two previous stimuli. This article ends with an activity to apply this theory.